PEMBERIAN AKAR PASAK BUMI (Eurycoma longifolia Jack.) PADA INDUK LAKTASI UNTUK MENINGKATKAN BOBOT BADAN ANAK MENCIT (Makara Journal of Science, 2009)
The Effect of Administration of Pasak Bumi (Eurycoma longifolia Jack.) Roots on Lactating Mice to Increase Body Weight Pups. The roots of Eurycoma longifolia Jack have been used as a traditional medicine for aprodisiac. The effects of the root extract of E. longifolia Jack were studied on lactating mice. Each mice was administered metanol extract and its derived fractions at dose 500 mg/kg rat body weight for 21 consecutive days in lactation period. Control positive group received Moloco+B12 at dose 0,13 g/kg rat body weight, negative control (placebo) group received 2 ml/kg rat body weight of aquadest daily and normal control group. No differences between normal control, negative control, positive control, and metanol extract and its derived fractions. The administration methanol-water fraction to lactating mice increasing body weight mice pups similar to Moloco+B12.